Analisis Statik Suspension Corong Calmp Bracket Dengan Metode Pengecoran Logam Permanent Mold Casting Logam Di PT. Putra Pandawa Yudhistira - Ikhwan Aditya (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the static strength of the suspension corong clamp bracket components used as cable supports in electric pole installations, focusing on design evaluation and durability. The research was conducted through simulations using SolidWorks software, emphasizing four key mechanical parameters: stress, displacement, strain, and factor of safety. The material used in the simulation was AISI 1045. The results of the analysis show that the maximum stress value of 2.224 × 10³ N/m² is still below the yield strength, with a maximum displacement of 9.550 × 10⁻⁷ mm, a maximum strain of 3.949 × 10⁹, and a factor of safety value of 2.383 × 10⁵. All of these results fall within the safe limits, indicating that the component's design can withstand the working load without the risk of failure. However, the highest displacement occurs at the suspension corong area, suggesting the need for reinforcement in this area to enhance rigidity. This research provides valuable contributions as a basis for validating the strength of the suspension corong clamp bracket and as a reference for product development at PT. Putra Pandawa Yudhistira. Keywords: suspension corong clamp bracket, SolidWorks, static simulation Abstrak Penelitian ini bertujuan untuk menganalisis kekuatan statik dari komponen suspension corong clamp bracket yang digunakan sebagai penyangga kabel pada instalasi tiang listrik, dengan fokus pada evaluasi desain dan ketahanan. Penelitian dilakukan melalui simulasi berbasis perangkat lunak SolidWorks dengan fokus pada empat parameter mekanik utama seperti stress, displacement, strain dan factor of safety, material yang digunakan dalam simulasi adalah AISI 1045. Hasil analisis menunjukkan bahwa nilai tegangan maksimum 2,224 x 103 N/m2 masih berada di bawah yield strength displacement maksimum sebesar 9,550 × 10⁻⁷ mm, regangan maksimum sebesar 3,949 × 10⁹, dan nilai FOS sebesar 2,383 × 10⁵. Seluruh hasil tersebut berada dalam batas aman, yang berarti desain komponen mampu menahan beban kerja tanpa risiko kegagalan. Namun, displacement tertinggi terjadi pada bagian suspension corong, sehingga disarankan dilakukan penebalan pada area tersebut untuk meningkatkan kekakuan. Penelitian ini memberikan kontribusi penting sebagai dasar validasi kekuatan suspension corong clamp bracket serta sebagai acuan pengembangan produk di PT. Putra Pandawa Yudhistira. Kata Kunci : suspension corong clamp bracket, SolidWorks, simulasi static